Exploration for analysis of medicinal foods used to manage dyslipidaemia in Sri Lankan traditional medicine - De silva, Damean; Senarath, Upul; Perera, Pathirage Kamal (Journal of Medicinal Herbs and Ethnomedicine, 2023)
The medicinal foods used to manage non-communicable diseases in Sri Lankan traditional medicine are slowly but steadily disappearing from the country due to many reasons. This study is the first stage of the research project aimed to explore and analyze the medicinal foods used to manage dyslipidaemia in traditional medical practices of Sri Lanka. A qualitative study covering the whole island was conducted cross-sectionally, supplemented by a document review including ancient textbooks and talipot palm (Corypha umbraculifera) leaf manuscripts. The study included all the registered traditional medical practitioners of the country, more than 55 years of age. Practitioners with poor memory and feeble health and those who were not in current practice were excluded. The first participant was selected purposively and the rest by using the snowball sampling technique. The investigator administered, validated, open-ended, semistructured questionnaire was the tool used, and the interviews were conducted face to face or using either telephone, zoom, or WhatsApp technology. The saturation was achieved by the 25th participant and data were analysed using the framework analysis technique. Nine medicinal foods including three herbal congees, one herbal beverage, one green leaf salad, and four curry preparations with antidyslipidaemic effects were explored. Sri Lankan native medicine possesses many medicinal foods with antidyslipidaemic effects and they should be explored, scientifically studied, and used as evidence-based management for the smooth control of diabetes mellitus.